2021
DOI: 10.1021/acsinfecdis.1c00057
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Challenges in Developing a Cryptosporidium Controlled Human Infection Model for Testing Antiparasitic Agents

Abstract: Cryptosporidiosis is a leading cause of moderate-to-severe diarrhea in low- and middle-income countries, responsible for high mortality in children younger than two years of age, and it is also strongly associated with childhood malnutrition and growth stunting. There is no vaccine for cryptosporidiosis and existing therapeutic options are suboptimal to prevent morbidity and mortality in young children. Recently, novel therapeutic agents have been discovered through high-throughput phenotypic and target-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 68 publications
4
8
0
Order By: Relevance
“…Challenges involving in vitro and in vivo models during the development of therapeutics for Cryptosporidium are extensively reviewed elsewhere (Jumani et al 2021 ; Manjunatha et al 2016 ). Briefly, using the mouse stem cell-derived intestinal epithelial monolayers, long-term C. parvum growth can be supported.…”
Section: Advanced Methods Of Oocysts Generation In Vitro Processing A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Challenges involving in vitro and in vivo models during the development of therapeutics for Cryptosporidium are extensively reviewed elsewhere (Jumani et al 2021 ; Manjunatha et al 2016 ). Briefly, using the mouse stem cell-derived intestinal epithelial monolayers, long-term C. parvum growth can be supported.…”
Section: Advanced Methods Of Oocysts Generation In Vitro Processing A...mentioning
confidence: 99%
“…Various novel in vivo animal models for parasite infection has been depicted elsewhere (Costa et al 2012 ; Lee et al 2019 ; Sateriale et al 2019 ). A recent review describes a controlled human model named CHIM (controlled human infection model) in volunteers for accelerated and robust drug discovery (Jumani et al 2021 ). Despite initial success in animal model-related studies, host specificity of the parasite, different symptoms, and diverse infection patterns should be kept in mind while addressing the issue in humans.…”
Section: Cryptosporidium Virulence Factors and Host Immune S...mentioning
confidence: 99%
“…In considering the re-establishment of the Cryptosporidium CHIM (525), one element that merits careful consideration is long-term safety risks of volunteers. In the studies conducted in the 1990s and early 2000s, there were no reported safety assessments of adverse events related to challenge beyond 60 days.…”
Section: The Cryptosporidium Human Challenge Modelmentioning
confidence: 99%
“…Several methods have been reported for perpetual propagation of C. hominis or C. parvum in cell culture(522)(523)(524), but these are not widely available nor used routinely. More recent epidemiology studies highlighting the burden of Cryptosporidium in low-and middle-income countries (LMICs) have rekindled the interest in this model for the purposes of testing drug and vaccine candidates for treatment or prevention of infection with the parasite(525). Studies of the natural history of cryptosporidiosis in LMIC populations demonstrate there are fewer infections among older children(502), suggesting that adaptive immunity induced by a vaccine is achievable.…”
mentioning
confidence: 99%
“…It is feasible that the clinical pathway for anticryptosporidial NCEs may diverge between the different target populations and use cases, and therefore, these studies could serve as a small-scale first pass to determine proof-of-concept efficacy of NCEs before a large financial investment in specific studies involving immunocompromised patients or young children. Although there is interest and precedence of CHIM for cryptosporidiosis [ 42 ], the most recent studies were conducted nearly two decades ago, and new regulatory requirements present unique challenges that complicate the re-establishment of this model [ 43 ▪ ].…”
Section: Clinical Trial Of Clofazimine and Lessons For Future Proof-of-concept Studiesmentioning
confidence: 99%